A systematic review and meta-analysis of the association between the apolipoprotein E genotype and delirium. (April 2016) - Adamis, Dimitrios; Meagher, David; Williams, John; Mulligan, Owen; McCarthy, Geraldine
Abstract : The role of apolipoprotein E ( APOE ) in Alzheimer's disease and other dementias has been investigated intensively. However, the relationship between APOE and delirium has only recently been explored in studies that have included relatively small samples. A meta-analysis of the published pooled data is timely to explore the relationship between APOE and delirium and to inform further research in this topic. PubMed, EBSCOhost, Google Scholar, Scopus, all EBM Reviews (OVID) and the Cochrane Database of Systematic Reviews were searched with relevant keywords and from the references of relevant papers. Ten papers were found that examined the relationship between APOE and delirium. Data were extracted from eight of them and pooled for meta-analysis using random effects with R software. Data from 1762 participants, of whom 479 (27.2%) were diagnosed with delirium, showed low heterogeneity ( Q =13.11, d.f. =7, P =0.07; I 2 =44.86%). The possession of the APOE ε4 allele has a small (log odds ratio: 0.18, 95% confidence interval: 0.23–0.59), nonsignificant ( P =0.38) effect on the presence of delirium. No publication bias was identified. The metapower of the pooled data was low ( α =0.05, power=0.65). On analysing the studies to date, it seems that there is no association between APOE and the occurrence of delirium. We suggest that further studies are needed with greater number of patients to clarify any association as well as to examine for other patterns of association including relevance for subgroups of patients who develop delirium and for effects on the phenotype of delirium and the outcomes.